Revisiting the 'sterilising cure' terminology: a call for more patient-centred perspectives on HIV cure-related research - Luke Newton; Raúl Necochea; David Palm; Jeff Taylor; Liz Barr; Hursch Patel; Anshula Nathan; Jo Gerrard; Laurie Sylla; Brandon Brown; Karine Dubé (Elsevier, 2019)
The literature on HIV therapeutics research is rife with terminology associating 'sterilisation' with HIV cure. We find connotations of the word 'sterilising' problematic for the HIV cure research field. In this viewpoint, we review associations of sterilising with concepts of disinfection or cleansing, as well as coerced sterilisation. We discuss emerging findings from socio-behavioural research that show aversion from people living with HIV towards the 'sterilising cure' nomenclature. We call for more collaborations with people with HIV as partners to help define what would be a more acceptable terminology for describing an HIV cure.